Heritability and Combining Ability of Some Vegetative and Yield Characteristics of Promising Arabica Coffee Varieties in Indonesia - Ari Wibowo; Miftahur Rizqi Akbar; Ucu Sumirat (Indonesian Coffee and Cocoa Research Institute, 2022)
Breeding for high yielding and good quality arabica coffee is the direction of the coffee breeding program in Indonesia. Hybridization becomes the important step to select promising genotypes from the genetic variability to achieve those goals. This research aimed to study heritability and combining ability of vegetative and yield characteristics of arabica coffee offspring. This research was conducted in randomized complete block design with three replications at Andungsari Experimental Station, East Java. The materials consisted of five parents of arabica coffee namely BP 542A(P1), P88(P2), S795(P3), HDT(P4), GEISHA(P5), and ten F1 hybrids as the offspring. The results showed that the narrow-sense heritability of leaf width was categorized as high. P3 and P5 varieties had the highest general combining ability (GCA) value for internode length, cluster number, and cherries number. These results indicated that both parental lines had potential as parents for the breeding program. The highest value of specific combining ability (SCA) for cherry size and leaf size was shown in crossing combination of P1×P3 and P2×P3. While, the crossing combination of P3×P4 showed the highest SCA value for cluster number, internode length, and cherries number per branch. From this crossing combination, high yielding promising lines can be obtained.